Instructional Management of English Teaching in Non-English Departments in Indonesia - Wiharjo, Cahyadi; Suryawirawan, Ade (Journal of English Language and Education, 2026)
This study examines the instructional management of English teaching across non-English departments in Indonesian higher education. It aims to explore instructional strategies, implementation practices, and challenges across diverse academic disciplines, including nursing, pharmacy, psychology, computer science, and international trade. A qualitative case study was conducted at Universitas YPIB over a three-month period. Data were collected through classroom observations, semi-structured interviews, and document analysis involving six lecturers and thirty students selected through purposive sampling. The findings reveal that effective instructional management requires adaptive teaching strategies, the integration of English for Specific Purposes (ESP), and alignment with disciplinary needs. However, several challenges persist, including varying levels of students’ English proficiency, limited institutional support, and the absence of a standardized curriculum. This study highlights the importance of flexible instructional planning and cross-disciplinary collaboration to enhance teaching effectiveness. It contributes to the development of instructional management practices in higher education, particularly in the Indonesian context. Furthermore, this study offers a cross-disciplinary perspective by integrating instructional management and ESP within a single institutional context.